Suffering, psychological distress, and well‐being in Indonesia: A prospective cohort study. (18th March 2022) - Ho, Samuel; Cook, Kaye V.; Chen, Zhuo Job; Kurniati, Ni Made Taganing; Suwartono, Christiany; Widyarini, Nilam; Wong, Paul T. P.; Cowden, Richard G.
Abstract: Research on the subjective experience of suffering has typically focussed on older clinical samples living in Western, educated, industrialised, rich, and democratic (WEIRD) countries. To further extend the existing body of empirical research on suffering to less WEIRD contexts, we use three waves of data (Wave 1: December 2020; Wave 2: January 2021; Wave 3: February 2021) from a sample of nonclinical Indonesian adults ( n = 594) to examine associations between suffering, two indices of psychological distress, and 10 facets of well‐being. In our primary analysis, we estimated a series of multiple regression models that adjusted for a range of sociodemographic characteristics, financial and material stability, religious/spiritual factors, prior values of overall suffering, and prior values of each outcome assessed in Wave 1. Results indicated that overall suffering assessed in Wave 2 was associated with an increase in both indices of psychological distress and a decrease in eight facets of well‐being assessed in Wave 3. Using a similar analytic approach, results from a secondary analysis indicated that higher scores on both indices of psychological distress and lower scores on seven of the well‐being facets assessed in Wave 2 were associated with worse subsequent overall suffering assessed in Wave 3. These findings contribute to empirical literature on the implications of suffering for well‐being.